Tindak Tutur Asertif dalam Naskah Nota Pembelaan: Pendekatan Linguistik Korpus - Resty, Shilvana Dwi; Novia Juita (Universitas Negeri Padang, 2024)
This research is motivated by the use of language in communicating using speech that expresses the truth. This research aims to describe (1) the characteristics of each type of assertive speech act in the defense note text and (2) the politeness principles of assertive speech acts in the defense note text. This research uses a qualitative descriptive method. The research data is in the form of sentences conveyed in the text of the defense note in the criminal trial for the murder of Brigadier Yoshua Hutabarat, including Ferdy Sambo, Kuat Ma'ruf, Putri Candrawathi, Richard Eliezer, and Ricky Rizal. Data collection in this research used free, interactive listening using the KORTARA application. The data analysis technique used is computational linguistics in accordance with the corpus processing application used. Based on the research results, it was found that, first, the types of assertive speech acts, namely stating, informing, complaining, reporting, and suggesting. Second, the principles of politeness in assertive speech acts, namely the maxims of simplicity, wisdom, respect, consensus and sympathy.